Comparative Efficacies of Long-Term Serial Transplantation of Syngeneic, Allogeneic, Xenogeneic, or CTLA4Ig-Overproducing Xenogeneic Adipose Tissue-Derived Mesenchymal Stem Cells on Murine Systemic Lupus Erythematosus - Eun Wha Choi D. V. M., Ph.D.; Hee Woo Lee; Il Seob Shin; Ji Hyun Park; Tae Won Yun; Hwa Young Youn; Sung-Joo Kim M.D., Ph.D. (Cell Transplantation, 2016)
Allogeneic and xenogeneic transplantation are suitable alternatives for treating patients with stem cell defects and autoimmune diseases. The purpose of this study was to compare the effects of long-term serial transplantation of adipose tissue-derived mesenchymal stem cells (ASCs) from (NZB × NZW) F1 mice (syngeneic), BALB/c mice (allogeneic), or humans (xenogeneic) on systemic lupus erythematosus (SLE). The effects of transplanting human ASCs overproducing CTLA4Ig (CTLA4Ig-hASC) were also compared. Animals were divided into five experimental groups, according to the transplanted cell type. Approximately 500,000 ASCs were administered intravenously every 2 weeks from 6 to 60 weeks of age to all mice except for the control mice, which received saline. The human ASC groups (hASC and CTLA4Ig-hASC) showed a 13-week increase in average life spans and increased survival rates and decreased blood urea nitrogen, proteinuria, and glomerular IgG deposition. The allogeneic group also showed higher survival rates compared to those of the control, up to 40, 41, 42, 43, 44, 45, 52, and 53 weeks of age. Syngeneic ASC transplantation did not accelerate the mortality of the mice. The mean life span of both the syngeneic and allogeneic groups was prolonged for 6–7 weeks. Both human ASC groups displayed increased serum interleukin-10 and interleukin-4 levels, whereas both mouse ASC groups displayed significantly increased GM-CSF and interferon-γ levels in the serum. The strongest humoral immune response was induced by xenogeneic transplantation, followed by allogeneic, CTLA4Ig-xenogeneic, and syngeneic transplantations. Long-term serial transplantation of the ASCs from various sources displayed different patterns of cytokine expression and humoral responses, but all of them increased life spans in an SLE mouse model.